Seismic versus aseismic slip for the 2023 Kahramanmaraş earthquake doublet - Rumeng Guo; Xiongwei Tang; Yijun Zhang; Wenting Zhang; Ming Qin; Jianqiao Xu; Jiangcun Zhou; Xuhao Zou; Heping Sun (Nature Communications)
Abstract Interplay between seismic and aseismic slip could shed light on the frictional properties and seismic potential of faults. The well-recorded 2023 Kahramanmaraş earthquake doublet provides an excellent opportunity to understand their partitioning on strike-slip faults. Here, we utilize InSAR and strong motion data to derive the coseismic rupture during the doublet, ~4-month postseismic afterslip, and slip distributions of two Mw>6.0 aftershocks. Our results show that afterslip appears to be complementary to coseismic slip and aftershocks, accounting for ~11.3% of the coseismic moment. Aftershocks mainly fall within the regions of positive Coulomb stresses caused by afterslip and follow a temporal decay similar to that of afterslip, indicating that aftershock production is the failure of small asperities loaded by the afterslip. The early postseismic afterslip is released ~93.7% aseismically and ~6.3% seismically by aftershocks. Our modeling results thus depict a complex fault system with highly variable slip patterns and stresses.